2018
DOI: 10.20944/preprints201812.0095.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate Change Impact On Rice Production in Pakistan: An ARDL-Bounds Testing Approach to Cointegration

Abstract: This research paper aims to examine the relationship between CO2, temperature, area, fertilizers and rice production in Pakistan. This study used Augmented Dickey Fuller (ADF) and Phillips Perron (PP) unit root tests to check the order of integration of each variable. The cointegration analysis with ARDL bounds testing approach is used to examine the impact of climate change on rice production in Pakistan over time series data from the period 1968 to 2014. The parameter stability test of the model is also chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The findings of this study arein agreement with those of Chandio, Jiang, and Magsi (2018), who analyzed the effect of support price on wheat production in Pakistan, and found that land area and fertilizer have significantly positive and positive impacts, respectively, on wheat production. Specifically, their results showed that an increase of 1% in the land area cultivated and fertilizer usage will increase wheat production by 0.78 and 0.19%, respectively.…”
Section: Impact Of Climatic and Non-climatic Variables On Maize Output Supply Responsesupporting
confidence: 92%
“…The findings of this study arein agreement with those of Chandio, Jiang, and Magsi (2018), who analyzed the effect of support price on wheat production in Pakistan, and found that land area and fertilizer have significantly positive and positive impacts, respectively, on wheat production. Specifically, their results showed that an increase of 1% in the land area cultivated and fertilizer usage will increase wheat production by 0.78 and 0.19%, respectively.…”
Section: Impact Of Climatic and Non-climatic Variables On Maize Output Supply Responsesupporting
confidence: 92%